The Influence of Digital Literacy on the Computational Thinking Skills of Fifth Grade Elementary Students - Reza Vransiskaa; Yasir Arafat; Murjainah Murjainah (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The purpose of this study is to examine how digital literacy affects the computational thinking skills of fifth-grade students at SDN 140 Palembang. Digital literacy is becoming an increasingly important ability in the current era, particularly in facilitating logical thinking and problem-solving processes using technology gadgets. This study employs a quantitative approach with a quasi-experimental design of the Non-equivalent Control Group Type. The research subjects were divided into two groups: the experimental class (V.A), which received technology-based learning treatment, and the control class (V.B), which received conventional learning. The data collection tool was a computational thinking questionnaire with 20 statements based on four major indicators: issue decomposition, algorithmic thinking, pattern identification, and abstraction and generalization. Pretests and posttests were used to collect data, which was then analyzed with a t-test to see if there was a significant difference between the two groups. The study's findings reveal that digital literacy has a considerable impact on student computational thinking skills. Students who received technology-based learning demonstrated greater improvement in computational thinking skills than students who learned using traditional methods. This research suggests that digital literacy is vital in helping elementary school students acquire computational thinking skills.